Relationship between fluid loss variation and physical activity during official games in elite soccer players - Djaoui, L.; Pialoux, V.; Vallance, E.; Owen, A.; Dellal, A. (Revista Internacional de Ciencias del Deporte, 2018)
The aim of the present study was to analyse the relationships between fluid ingestion, changes in body mass and physical activity amongst elite soccer players. 32 elite French soccer players were divided into six playing positions: goalkeepers (GK), central defenders (CD), full backs (FB), central midfielders (CM), wide midfielders (WM) and forwards (FW) and participated in official friendly matches within two consecutive pre-season periods. Body mass changes and fluid ingestion were recorded before, during and just after the matches. Time-motion characteristics were also analysed. Players ingested 1.4±0.6 L of fluids during matches and lost 1.4±0.6 kg at the end of the games. WM lost more weight than GK, FB and FW (p<0.05) and CM lost more weight than GK (p<0.05). Furthermore, CD covered significantly less total distance, high (HI) and very high intensity running distance than all other playing positions excluding GK (p<0.05); and WM covered greater distances at HI than all other playing positions. No differences were found in fluid ingestion between playing positions. The results of this study indicate that sweat loss was significantly different when comparing across various playing positions. As a result, sweat lost may be more influenced by HI activity during a game than other physical activity within game scenarios. Therefore, players with the highest amount of HI activities during a match should even more pay attention to their rehydration.